A staff development program for promoting change in Higher Education teaching and learning practices - Ramos, Fernando
This paper presents and discusses a faculty development program being carried out at the University of Aveiro, aiming at providing academics with essential skills in areas such as teaching best practices, student-centered curriculum design, collaborative learning and the adoption of ICT/Intemet technologies.